Effects of tillage options on soil physical properties and cassava-dry-matter partitioning - Figueiredo, Priscila Gonzales [UNESP]; Bicudo, Silvio Jose [UNESP]; Chen, Songbi; Fernandes, Adalton Mazetti [UNESP]; Tanamati, Fabio Yomei [UNESP]; Djabou-Fondjo, Astride Stephanie Mouafi (My University, 2020)
Conservation tillage is efficient at reducing soil degradation, but affects soil physical properties, andleads to soil compaction, negatively impacting root production, and so it is rarely adopted by cassavacultivators. The objective of this study was to evaluate the dry-matter partitioning (DMP) during a fullcassava season under different tillage methods. The effects of minimum tillage (MT), conventional tillage (CT) and no-tillage (NT) on soil water content, soil penetration resistance, macroporosity, microporosityand total porosity were evaluated at 70, 120, 230, 300 and 350 days after planting (DAP). Additionally, the DMP in cassava plants was evaluated every 30 days until 360 DAP at Botucatu, Brazil on an Alfisolsoil. Our result revealed that the tillage type affected soil penetration resistance, macroporosity andtotal porosity as well as the dry matter content (DMC) on cassava leaf, stem, root and planted cutting.No significant difference was observed in total DMC. However, DMP differed significantly between 150 and 210 DAP, corresponding respectively to the root-thickening phase end and the dormancy phasebeginning. The highest DMC of stem and planted cutting was observed in NT-developed plants. ShootDMC was positively correlated with soil penetration resistance. CT and MT did not differ in root yield;hence, MT should be adopted instead of CT, as an effort to control soil erosion. NT increases the soilpenetration resistance, and results in greater accumulation of DM in the stem and planted cutting thanin the roots. Data suggest that increased soil penetration resistance under NT can decrease cassava rootgrowth and induce the stem and planted cutting to play the role of storage organs.
Keywords: conventional tillage; Manihot esculenta; minimum tillage; no-tillage